2012
DOI: 10.1016/j.athoracsur.2012.01.105
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Outcomes for Risk-Stratified Pediatric Cardiac Surgical Operations: An Analysis of the STS Congenital Heart Surgery Database

Abstract: Background. We evaluated outcomes for groups of risk-stratified operations in The Society of Thoracic Surgeons Congenital Heart Surgery Database to provide contemporary benchmarks and examine variation between centers. Methods. Patients undergoing surgery from 2005 to 2009 were included. Centers with more than 10% missing data were excluded. Discharge mortality and postoperative length of stay (PLOS) among patients discharged alive were calculated for groups of risk-stratified operations using the five Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 12 publications
(18 reference statements)
3
142
1
Order By: Relevance
“…We observed a range of extubation failure rates across the seven participating centers in our study, from 8% -23%, also consistent with the data from the PC4 registry, which reported a range of 5% -22% [10]. Further, the only retrospective single center study that focused on a heterogeneous population of neonates who underwent cardiac surgery published an extubation failure rate of 17.5% [11]. This variation in extubation failure occurrence rates across centers suggests an opportunity for institutional quality assurance initiatives aimed at decreasing the occurrence of this frustrating and potentially life-threatening complication.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We observed a range of extubation failure rates across the seven participating centers in our study, from 8% -23%, also consistent with the data from the PC4 registry, which reported a range of 5% -22% [10]. Further, the only retrospective single center study that focused on a heterogeneous population of neonates who underwent cardiac surgery published an extubation failure rate of 17.5% [11]. This variation in extubation failure occurrence rates across centers suggests an opportunity for institutional quality assurance initiatives aimed at decreasing the occurrence of this frustrating and potentially life-threatening complication.…”
Section: Discussionsupporting
confidence: 77%
“…Table 2 (online), organized by STAT mortality category. [11,12] The most common operations performed were the arterial switch procedure (n=60) and the Norwood procedure (n=47).…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paediatricians with expertise in cardiology, however, may not be the first point of contact for the deteriorating infant with CHD, and there may be potential for learning from related secondary care examples, such as scoring tools that have been deployed in A&E and utilised by non-specialist HPs to detect signs of deterioration in presenting children. 146 Finally, at present the focus of national and international audit remains on 30-day mortality rates for paediatric cardiac surgery 68,69,147 and we note that additional audit metrics focusing on the postdischarge stage of the patient journey may be a useful lever for quality improvement in the future.…”
Section: Implications Of Our Findingsmentioning
confidence: 99%
“…68 These early mortality outcomes have improved over time to the current, historically low, levels. 4 However, although important, these outcome measures are relatively limited in scope, and longer-term measures of outcome and metrics such as morbidity or complications are also essential to consider in quality assurance and improvement.…”
Section: Introductionmentioning
confidence: 99%